2019
DOI: 10.1002/jpln.201800223
|View full text |Cite
|
Sign up to set email alerts
|

Combination of agricultural waste compost and biofertilizer improves yield and enhances the sustainability of a pepper field

Abstract: Application of plant growth‐promoting rhizobacteria (PGPR) has been considered as an environmentally friendly method for crop yield promotion as well as plant disease management. Efforts have been devoted to unraveling mechanisms involved in bacteria–plant and bacteria–pathogen interactions. However, little is known on the effect of the interaction among PGPR, soil, and plant. We compared growth and yield promotion capacity of biofertilizer Ning Shield, a consortium of bacterial preparation used as a biofertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 48 publications
5
18
0
Order By: Relevance
“…The additional bacteria in M2 treatment increased the soluble sugar content of blueberry fruit by 4.21%, the content of vitamin C by 17.31%, the content of soluble solids by 2.41%, and the content of soluble protein by 21.65%, while titratable acid in fruit was reduced by 10.81% (Figure 2). These results are consistent with the previously report, in which the application of the microbial consortium improved the fruit quality of pepper (Yu et al., 2019). It has also been reported that the beneficial microorganisms are able to increase the accumulation of soluble sugar in plants by enhancing photosynthesis (Jha & Subramanian, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…The additional bacteria in M2 treatment increased the soluble sugar content of blueberry fruit by 4.21%, the content of vitamin C by 17.31%, the content of soluble solids by 2.41%, and the content of soluble protein by 21.65%, while titratable acid in fruit was reduced by 10.81% (Figure 2). These results are consistent with the previously report, in which the application of the microbial consortium improved the fruit quality of pepper (Yu et al., 2019). It has also been reported that the beneficial microorganisms are able to increase the accumulation of soluble sugar in plants by enhancing photosynthesis (Jha & Subramanian, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…Nadeem and colleagues (2014) showed that AMF and PGPR can regulate mineral nutrition by solubilizing nutrients in the soil and producing plant growth regulators (i.e., hormones). Several studies have indicated that compost, AMF and PGPR improve plant growth through the assimilation of immobile soil nutrients such as N and P (Yadav et al, 2013;Baslam et al, 2014;Al-Karaki, 2016;Barje et al, 2016;Frosi et al, 2016;Yang et al, 2018;Raklami et al, 2019;Yu et al, 2019). Here we showed that inoculated and amended date palm plants had considerably higher mineral nutrient content (P and N) as compared to controls under water deficit conditions allowing higher plant performance.…”
Section: Discussionmentioning
confidence: 47%
“…Bioorganic fertilizer (BIO) is an organic amendment prepared by secondary solid-state fermentation of organic materials, with the addition of specific functional microbial strains. It has been widely used in apple (Wang et al 2016 ), banana (Shen et al 2019 ), pepper (Yu et al 2019 ), and kiwi (Liu et al 2020c ) orchards to improve soil biological fertility, and restructure soil microflora. Soil microbes have an enormous impact on soil fertility, ecosystem sustainability, as well as plant health and growth (Gu et al 2019 ; Li et al 2021 ; Ma et al 2018 ; Zhang et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%